Analysis of Practical Goals of Learning a Foreign Language (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the goals of foreign language education have been widely discussed in methodological literature, the term applied methodology has caused more than one association among teachers, and opinions are given about concepts of different sizes and forms.